1997
DOI: 10.1021/om970679o
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Infrared Spectral Studies of Photochemically Induced Oxidative Addition of Benzene to trans-RhCl(CO)(PMe3)2

Abstract: Time-resolved infrared and time-resolved optical spectroscopy were used to examine the pathway-(s) by which 355 nm photolysis of the rhodium(I) species trans-RhCl(CO)(PMe 3 ) 2 (1) in benzene leads to the C-H oxidative-addition product (Ph)(H)RhCl(CO)(PMe 3 ) 2 (2). Two reaction pathways to the formation of 2 were found. One of these was the "prompt" formation (<150 ns) of 2, the apparent result of a direct reaction of the electronic excited state of the four-coordinate species 1 with the C 6 H 6 solvent. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…[16][17][18][19][20] This assignment can be confirmed by a similar experiment with deuterated n-[D 18 ]octane in which a new band at ñ = 1466 cm À1 was observed that results from n(Rh III ÀD) vibrations in addition to the bands at ñ = 1963 and 1985 cm À1 , whereas the band at ñ = 2065 cm À1 was absent ( Figure S2). [16][17][18][19][20] This assignment can be confirmed by a similar experiment with deuterated n-[D 18 ]octane in which a new band at ñ = 1466 cm À1 was observed that results from n(Rh III ÀD) vibrations in addition to the bands at ñ = 1963 and 1985 cm À1 , whereas the band at ñ = 2065 cm À1 was absent ( Figure S2).…”
Section: Spectroscopic Investigations and Reaction Mechanismsupporting
confidence: 66%
See 1 more Smart Citation
“…[16][17][18][19][20] This assignment can be confirmed by a similar experiment with deuterated n-[D 18 ]octane in which a new band at ñ = 1466 cm À1 was observed that results from n(Rh III ÀD) vibrations in addition to the bands at ñ = 1963 and 1985 cm À1 , whereas the band at ñ = 2065 cm À1 was absent ( Figure S2). [16][17][18][19][20] This assignment can be confirmed by a similar experiment with deuterated n-[D 18 ]octane in which a new band at ñ = 1466 cm À1 was observed that results from n(Rh III ÀD) vibrations in addition to the bands at ñ = 1963 and 1985 cm À1 , whereas the band at ñ = 2065 cm À1 was absent ( Figure S2).…”
Section: Spectroscopic Investigations and Reaction Mechanismsupporting
confidence: 66%
“…After 10 min, two new bands appear simultaneously at ñ = 1986 and 2065 cm À1 , which can be assigned to the n(Rh III ÀCO) and n(Rh III ÀH) modes, respectively. [16][17][18][19][20] This assignment can be confirmed by a similar experiment with deuterated n-[D 18 ]octane in which a new band at ñ = 1466 cm À1 was observed that results from n(Rh III ÀD) vibrations in addition to the bands at ñ = 1963 and 1985 cm À1 , whereas the band at ñ = 2065 cm À1 was absent ( Figure S2). Alternatively, these bands might stem from two different intermediate Rh complexes that contain either CO or H as the ligand (vide infra).…”
Section: Spectroscopic Investigations and Reaction Mechanismsupporting
confidence: 66%
“…TRIR experiments using the step-scan technique demonstrated that 355 nm flash photolysis of III in benzene- d 6 solution under argon leads to a transient difference spectrum fully consistent with that seen for low-temperature FTIR experiments in this medium. A strong transient bleach at 1962 cm -1 and a new, broad absorbance at 2050 cm -1 corresponding to the formation of an intermediate were observed (supplemental Figure S-8) 1c…”
Section: Resultsmentioning
confidence: 99%
“…10−15 kcal mol -1 ) solvent molecule as a “token” ligand in place of the nominally empty coordination site. Picosecond spectroscopy has been used to study the solvation process itself, while the bimolecular reactions of solvated intermediates, which typically take place on a microsecond time scale, have been studied by a variety of methods such as photoacoustic calorimetry (PAC), , time-resolved UV−visible spectroscopy (TRUVVIS), and time-resolved infrared absorption spectroscopy (TRIR) . These reactions are analogous to steps in homogeneous catalytic processes in which a substrate molecule binds to a “coordinatively unsaturated” catalytic intermediate …”
Section: Introductionmentioning
confidence: 99%